A biosensing platform for sensitive detection of concanavalin A based on fluorescence resonance energy transfer from CdTe quantum dots to graphene oxide1. (27th August 2015) - Li, Yan; Shi, Fanping; Cai, Nan; Su, Xingguang
<x xml:space="preserve">Abstract</x> The sandwich method can detect different lectins simply by exchanging the carbohydrates functionalized on the quantum dots and graphene oxide.